2018
DOI: 10.1002/slct.201800154
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis on the Probability Density Distribution of Methane Hydrate Induction Times in Porous Media

Abstract: Hydrate‐based natural‐gas transport and storage have been proposed and developed because of the high safety and low cost, and hydrate reformation is a serious barrier for high‐efficiency natural‐gas hydrate exploitation. The hydrate formation induction time is a crucial kinetic parameter for both of the two fields. To clarify the hydrate formation and/or reformation induction characteristics, the effects of sub‐cooling, particle size, initial water saturation and memory effect on the stochastic induction time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Zi et al revealed that silica sands could reduce the induction time for methane hydrate in a water-in-oil emulsion. Wang and co-workers found that an increase in the particle size of sand significantly reduced the induction time for methane hydrate, while the induction time could be fitted to a log-normal distribution. However, Chen et al .…”
Section: Ngh Phase Equilibria and Kinetics Research In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…Zi et al revealed that silica sands could reduce the induction time for methane hydrate in a water-in-oil emulsion. Wang and co-workers found that an increase in the particle size of sand significantly reduced the induction time for methane hydrate, while the induction time could be fitted to a log-normal distribution. However, Chen et al .…”
Section: Ngh Phase Equilibria and Kinetics Research In Chinamentioning
confidence: 99%
“…It is believed that hydroxylated solids can form a new interface with melted water after hydrate decomposition due to the presence of impurities, while the interface is known as an “imprint”. Although several hydrate reformation studies have been conducted involving solid particles, the impurity imprinting mechanism has not been satisfactorily verified due to experimental visualization technology limitations. However, molecular dynamics simulations have confirmed the preference of hydrate nucleation on hydroxylated solid surfaces during the first formation, which could guide the verification of this mechanism.…”
Section: Ngh Phase Equilibria and Kinetics Research In Chinamentioning
confidence: 99%
“…Zi et al found that the presence of silica sand could greatly shorten the induction time of methane hydrate in the oil-in-water emulsion. Wang , et al increased the sand particle size and found that the induction time was significantly shortened. However, Chen et al reached a completely different conclusion: at the gas–water interface, the presence of sand particles could prevent methane gas from entering the water, inhibit the nucleation of hydrate, and lead to the increase of induction time.…”
Section: Introductionmentioning
confidence: 99%
“…The induction time of hydrate reformation is dramatically reduced owing to the presence of the memory effect. 2325 Many studies have proven that the memory effect could effectively promote hydrate reformation. 2630 These studies found that porous media can highlight the memory effect in hydrate reformation.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the first hydrate formation that reflects the stochastic nature of nucleation possesses a long induction time, implying that more time and energy must be consumed, which goes against the principle of cold storage at cost. , Therefore, many efforts, such as the use of surfactants and porous media, have been made to shorten the induction time. Sodium dodecyl sulfate (SDS), as a perfect surfactant for enhancing hydrate formation, is widely used, but there is no consensus on the characteristics of cyclic hydrate reformation (excluding the first hydrate formation from cyclic hydrate formation). The induction time of hydrate reformation is dramatically reduced owing to the presence of the memory effect. Many studies have proven that the memory effect could effectively promote hydrate reformation. These studies found that porous media can highlight the memory effect in hydrate reformation . However, it remains unclear and controversial as to whether the memory effect maintains stability upon cyclic hydrate reformation, and related research is not comprehensive, especially in SDS systems or porous media.…”
Section: Introductionmentioning
confidence: 99%